2005
DOI: 10.1158/1535-7163.mct-05-0167
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional targeting modalities in breast cancer gene therapy using adenovirus vectors controlled by α-lactalbumin promoter

Abstract: The breast-specific antigen A-lactalbumin is expressed in >60% of breast cancer tissues. To evaluate the effect of gene therapy for breast cancer by controlling adenovirus replication with human A-lactalbumin promoter, we investigated the activity of a 762-bp human A-lactalbumin promoter. A-Lactalbumin promoter showed significantly higher activity in MDA-MB-435S and T47D breast cancer cells than in normal breast cell lines or other tumor cell lines. We then developed two novel breast cancer -restricted replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Transcriptional targeting takes advantage of the fact that promoters of the genes which are exclusively expressed in cancer cells, could be used for specific expression of lethal genes in cancer cells. 37 Similar work, using Erb-B2, 38 PPAR-c1, 39 a-lactalbomin, 40 mammaglobin, 41 and L-plastin promoters 42 have been reported for specific expression of lethal gene in breast cancer cells. Erb-B2 promoter was used for specific expression of HSV-tk transgene in breast cancer cells, 38 but over-expression also occurs in other malignancies such as ovarian cancer and stomach cancer.…”
Section: Discussionsupporting
confidence: 60%
“…Transcriptional targeting takes advantage of the fact that promoters of the genes which are exclusively expressed in cancer cells, could be used for specific expression of lethal genes in cancer cells. 37 Similar work, using Erb-B2, 38 PPAR-c1, 39 a-lactalbomin, 40 mammaglobin, 41 and L-plastin promoters 42 have been reported for specific expression of lethal gene in breast cancer cells. Erb-B2 promoter was used for specific expression of HSV-tk transgene in breast cancer cells, 38 but over-expression also occurs in other malignancies such as ovarian cancer and stomach cancer.…”
Section: Discussionsupporting
confidence: 60%
“…Adenovirus-mediated gene therapy has been tested broadly in clinical trials, and tumor/tissue-restricted replicative adenovirus showed significant advantages over replication-deficient adenovirus (14,28,29). However, the single administration of PRRA ultimately results in failure due to inefficient viral distribution in tumor masses (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the promoter region of breast-specific α lacta albumin (ALA) has been employed to generate two CRAds: AdALAE1a with E1a under the control of ALA promoter and AdE1aALAE1b with both E1a and E1b genes driven by α lacta albumin promoter, respectively. AdE1aALAE1b inhibited tumor growth of hormoneindependent breast tumors in a mouse xenograft model [87].…”
Section: Albumin Promotermentioning
confidence: 97%